PENGARUH MODEL PEMBELAJARAN REACT DAN GUIDED DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA - Nia Risti Rahayu; Sumaji Sumaji (EDUPEDIA, 2017)
The purpose of this research were to know: (1) the effect of REACT learning model on the students’ understanding of mathematical concepts, (2) the effect of guided discovery learning model on students' understanding of mathematical concepts, (3) the difference in students’ mathematical concept understanding obtained by using REACT learning model and guided discovery learning. This research type was quasi experiment with entire class VII MTs Al-Islam Joresan as population and class VIIA and VIIB as sample. Class VIIA was taught  by using the REACT learning model and class VIIB was taught by using the guided discovery learning model. The instrument used was a question sheet of concept comprehension test and data collection the technique was test and documentation. The concept comprehension test results were analyzed using t test with significance level of 0.05. The results of the hypothesis test showed that the REACT learning model has an effect on the students’ understanding of mathematical concepts. In addition, the guided discovery learning model has an effect on the students’ understanding of mathematical concepts. Both REACT learning model and guided discovery learning model showed no difference in students’ mathematical concept understanding.